Biological Production of Distinct Carbon Pools Drives Particle Export Efficiency in the Southern Ocean - Yibin Huang; Andrea J. Fassbender (Geophysical Research Letters)
Abstract We use observations from the Southern Ocean (SO) biogeochemical profiling float array to quantify the meridional pattern of particle export efficiency (PEeff) during the austral productive season. Float estimates reveal a pronounced latitudinal gradient of PEeff, which is quantitatively supported by a compilation of existing ship‐based measurements. Relying on complementary float‐based estimates of distinct carbon pools produced through biological activity, we find that PEeff peaks near the region of maximum particulate inorganic carbon sinking flux in the polar antarctic zone, where net primary production (NPP) is the lowest. Regions characterized by intermediate NPP and low PEeff, primarily in the subtropical and seasonal ice zones, are generally associated with a higher fraction of dissolved organic carbon production. Our study reveals the critical role of distinct biogenic carbon pool production in driving the latitudinal pattern of PEeff in the SO.